Electronic cigarette use and its systemic repercussions - Carvalho, Marina Teixeira de; Rodrigues, Ana Clara Ferin; Rocha, Isabella Ribeiro da; Pereira, Luciano Penha (Seven Editora, 2023)
The electronic cigarette is a device composed of a heating element and a cartridge, filled with flavorings, nicotine and other elements, which, through a battery, generate vapor. The vaporized liquid, inhaled from a mouthpiece, provides sensations similar to that of tobacco smoke, delivering nicotine to the user in a less irritating way. It presents an alternative mechanism to combustion and allows the dosing of components, but its use is also associated with the development of heart and lung diseases. Thus, it is known that although the use of electronic cigarettes emerge. As an alternative to smoking, its real impact on the health of individuals is not yet fully elucidated. This summary exposes the systemic repercussions associated with the continuous use of FB and its effect on the user’s life. A literature review was performed using the PubMed platform, with research from the last 5 years, in Portuguese and English. DOI:https://doi.org/10.56238/alookdevelopv1-155